To find the equation that describes an infinite solution system with the equation \( y = 4x - 3 \), we need to identify equations that are equivalent to this equation.
The given equation can be rearranged to find the same line in different forms.
Starting from \( y = 4x - 3 \), we can multiply the entire equation by 2 to get:
\[ 2y = 8x - 6 \]
Rearranging this gives:
\[ 2y - 8x = -6 \]
Now let's look at the provided options:
- \( -2y + 8x = -6 \) (Not equivalent)
- \( 2y - 8x = -6 \) (Equivalent)
- \( 2y + 8x = -6 \) (Not equivalent)
- \( 2y - 8x = 6 \) (Not equivalent)
The equation that describes an infinite solution system with the equation \( y = 4x - 3 \) is:
2y − 8x = −6.